P330 Blunted heart rate reserve during vasodilator stress echocardiography in diabetic and renal failure patients. (17th January 2020) - Bellino, M; Ferraro, D; Silverio, A; Peluso, A P; Soriente, L; Provenza, G; Ascoli, R; Iuliano, G; Prota, C; Polito, M V; Cogliani, F; Maiellaro, F; et al.
Abstract: Funding Acknowledgements: None Background: A blunted heart rate reserve (HRR) during dipyridamole stress echo (SE) is a marker of cardiac autonomic dysfunction associated with poor outcome, independently of inducible ischemia, underlying coronary artery disease (CAD) and beta-blocker therapy. Patients with diabetes and/or renal failure have higher prevalence of underlying autonomic dysfunction. Aim. To assess the value of HRR in patients undergoing dipyridamole SE. Methods: We prospectively recruited a sample of 61 patients with known or suspected CAD (mean age 75 ± 10 years; 34 males, 55, 7%; 50% on beta-blockers at the time of testing). Coexistent atrial fibrillation or previous pacemaker implantation were considered as exclusion criteria. Three groups were identified a priori: non-diabetic with normal renal function (n = 43, Group 1); diabetics, with normal renal function (n = 14, Group 2); severely impaired renal function on dialysis (n = 4, Group 3). All patients underwent dipyridamole SE (0.84 mg/kg in 10"). Wall motion score Index (WMSI) was calculated with a 17-segment score of left ventricle, each segment scored from 1= normal to 4= dyskinetic. HRR was measured by ECG as the peak/rest HR ratio. Results: A positive SE (stress WMSI> rest WMSI) was present in 2 patients of Group 1 (4.7%), 4 of Group 2 (28.6%) and no patient in Group 3. Heart rate was different, although not significant, among the 3 groups both at rest (66.1 ± 11.1 vs 64.6 ± 8.5 vs 79.0 ± 8.0, p = 0.050) and at peak stress (83.8 ± 12.6 vs 75.3 ± 10.3 vs 86.5 ± 11.1, p = 0.059). Of note, HRR was statistically different among groups (1.29 ± 0.20 vs 1.19 ± 0.14 vs 1.09 ± 0.06, p < 0.047; see figure). There was no difference in HRR between patients off and on-beta-blockers (1.19 ± 0.16 vs 1.24 ± 0.24, p = 0.421) and with or without positive SE (1.20 ± 0.14 vs 1.25 ± 0.20, p = 0.530). Overall, HRR ≤ 1.17 (median value) was reported in 39.5% of Group 1, 71.4% of Group 2, and 100% of Group 3 pts (p = 0.024). No significant correlations between HRR and peak WMSI (p = 0.183) or age (0.062) were reported. Conclusion: HRR is frequently abnormal in patients referred for SE testing, especially in presence of concomitant diabetes and advanced renal failure. The blunted chronotropic response is a simple, imaging independent marker of cardiac autonomic dysfunction and may usefully complement the conventional evaluation with regional wall motion abnormalities during vasodilator SE.